2009
DOI: 10.1002/bem.20478
|View full text |Cite
|
Sign up to set email alerts
|

Specific absorption rate and electric field measurements in the near field of six mobile phone base station antennas

Abstract: In this article, the exposure to radio frequency electromagnetic fields was studied in close proximity (distances of 10, 100, 300, and 600 mm) to six base station antennas. The specific absorption rate (SAR) in 800 mm x 500 mm x 200 mm box phantom as well as unperturbed electric field (E) in air was measured. The results were used to determine whether the measurement of local maximum of unperturbed electric field can be used as a compliance check for local exposure. Also, the conservativeness of this assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Generally, a near-field is one wavelength (λ) or less away from the source of radiation, whereas a far-field is about two wavelengths (2λ) away from the antenna (Occupational Safety Health Administration, 1990). Toivonen et al (2019) demonstrated that the ICNIRP limit for localized exposure (2 W/kg) could be reached if the distance between the antenna and the body is <24 cm. As a consequence, when people hold their phones next to their heads or wear them on their bodies, they may be exposed to very intense near-field radiation from the device at close or touching distances.…”
Section: Factors Influencing Rf-emr's Biological Effectmentioning
confidence: 99%
“…Generally, a near-field is one wavelength (λ) or less away from the source of radiation, whereas a far-field is about two wavelengths (2λ) away from the antenna (Occupational Safety Health Administration, 1990). Toivonen et al (2019) demonstrated that the ICNIRP limit for localized exposure (2 W/kg) could be reached if the distance between the antenna and the body is <24 cm. As a consequence, when people hold their phones next to their heads or wear them on their bodies, they may be exposed to very intense near-field radiation from the device at close or touching distances.…”
Section: Factors Influencing Rf-emr's Biological Effectmentioning
confidence: 99%
“…Consequently, in the vicinity of EMF sources, various hazards for implant users need to be identified and evaluated, especially for users of AIMD. In the systematic considerations, the EMF influence on AIMD functions may be split into the following groups (where it is not excluded that they will present together): -influence on the electric circuit of the AIMD, -influence on the internal memory of the AIMD, -influence on mechanical structures -by heating, reposition, etc., Pacing inhibition (complete or temporary stop of pacing); the implant interprets electrical potentials from EMF electrodynamic interaction as the proper heart rate and stops the pacing, even in the absence of the intrinsic heart rate EAS systems [5,6]; induction hobs (25-34 kHz) [7]; GSM [6,[8][9][10]; vicinity of BTS [11,12]; MD gates [13]; MRI scanners (1.5 T) [6,14]; ESU [6,15] CP [11,12]; 3.4. 400 kV power lines [19]; 3.5.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in the area of base station SAR measurements have mainly focused on small base station products and antennas [Hamberg et al, 2003;Ilvonen et al, 2008]. Some results on SAR measurements for larger base station antennas are available [Cooper et al, 2002;Joseph and Martens, 2005;Gosselin et al, 2009;Toivonen et al, 2009], but these studies did not focus on the issues discussed in this article.…”
Section: Introductionmentioning
confidence: 99%